2018
DOI: 10.1002/cpdd.620
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a High‐Fat Meal on the Pharmacokinetics of the HIV Integrase Inhibitor Cabotegravir

Abstract: Cabotegravir is an integrase inhibitor in clinical development for the treatment and prevention of HIV infection using oral tablets for short-term, lead-in use before subsequent administration of a long-acting injectable formulation. This phase 1, single-center, randomized, 2 × 2 crossover study evaluated the effect of a high-fat meal on the pharmacokinetics (PK) of oral cabotegravir. Healthy adults received oral cabotegravir 30 mg as a single dose on 2 separate occasions, either after fasting or following a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
(52 reference statements)
0
6
0
1
Order By: Relevance
“…CAB has more favorable PK properties than other INSTIs. This includes its long plasma half-life of 30-40 h 8 , fast oral absorption (t max = 1.5-2 h) 16 , near-complete oral bioavailability 16,22 , and low DDI potential due to its high membrane permeability and low affinity for CYP450 9,10 . In humans, CAB is primarily eliminated unchanged in feces (up to 50% unchanged and 10% unidentified metabolites) and as glucuronide metabolites in urine (27%) 16 .…”
Section: Discussionmentioning
confidence: 99%
“…CAB has more favorable PK properties than other INSTIs. This includes its long plasma half-life of 30-40 h 8 , fast oral absorption (t max = 1.5-2 h) 16 , near-complete oral bioavailability 16,22 , and low DDI potential due to its high membrane permeability and low affinity for CYP450 9,10 . In humans, CAB is primarily eliminated unchanged in feces (up to 50% unchanged and 10% unidentified metabolites) and as glucuronide metabolites in urine (27%) 16 .…”
Section: Discussionmentioning
confidence: 99%
“…CAB has more favorable PK properties then other INSTIs. This includes its long plasma half-life of 30-40 h 8 , fast oral absorption (t max = 1.5-2 h) 16 , near-complete oral bioavailability 16, 22 , and low DDI potential due to its high membrane permeability and low affinity for CYP450 9, 10 . In humans, CAB is primarily eliminated unchanged in feces (up to 50% unchanged and 10% unidentified metabolites) and as glucuronide metabolites in urine (27%) 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Accuracy ranged from 14.8% to 8.0% bias. The complete analysis of cabotegravir with all the necessary parameters has been previously described …”
Section: Methodsmentioning
confidence: 99%
“…Cabotegravir is rapidly absorbed after oral administration and the previously reported geometric mean (95% confidence interval [CI]) of the area under the concentration‐time curve (AUC) was 146 (128–167) µg · h/mL with single‐dose administration of a 30‐mg tablet; it is slowly cleared with a long apparent terminal elimination half‐life (t 1/2 ) of 38.5 hours . Results from a recent food‐effect study revealed that both plasma cabotegravir AUC and maximum observed cabotegravir concentration (C max ) increase by 14% in the presence of a high‐fat meal . The PK parameters increased proportionally to dose from 5 to 30 mg but were less than proportional to dose from 30 to 60 mg .…”
mentioning
confidence: 99%
See 1 more Smart Citation